2016
DOI: 10.1038/pr.2016.47
|View full text |Cite
|
Sign up to set email alerts
|

Liganded retinoic acid X receptor α represses connexin 43 through a potential retinoic acid response element in the promoter region

Abstract: RXRα negatively regulates the transcription and expression by directly binding to the RARE in the promoter of Cx43. The RARE-like sequence harbored in the Cx43 promoter region may serve as a functional RARE in the retinoic acid (RA) signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…And the single nucleotide polymorphism rs2071166 located within a functional retinoic acid response element (Fig 1, repeating element with black background). 17,18 We identified two alleles (A and C) and three genotypes (AA, AC, and CC) at rs2071166 in both groups (Fig 2, Table 3). The frequency of Cx43 rs2071166 genotypes were 62.7% (AA), 21.3% (AC), 16% (CC) in patients with atrial septal defects and 67.0% (AA), 28.3% (AC), 4.7% (CC) in healthy controls ( Table 3).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…And the single nucleotide polymorphism rs2071166 located within a functional retinoic acid response element (Fig 1, repeating element with black background). 17,18 We identified two alleles (A and C) and three genotypes (AA, AC, and CC) at rs2071166 in both groups (Fig 2, Table 3). The frequency of Cx43 rs2071166 genotypes were 62.7% (AA), 21.3% (AC), 16% (CC) in patients with atrial septal defects and 67.0% (AA), 28.3% (AC), 4.7% (CC) in healthy controls ( Table 3).…”
Section: Resultsmentioning
confidence: 83%
“…18 The retinoic acid response element was critical in retinoic acid regulating Cx43 transcription activity and expression level. 18 Thus, we speculated that this single nucleotide polymorphism might change the efficiency of Cx43 transcription through damaging the function of the retinoic acid response element in Cx43. To further investigate our hypothesis, more molecular biology experiments such as luciferase transfection assay, electrophoretic mobility shift assay (EMSA), and transgenic knock-in animal models should be carried out to figure out the mechanism in CC genotype at rs2071166 affecting the retinoic acid response element in Cx43 and analyse the phenotype of the embryo heart.…”
Section: Discussionmentioning
confidence: 99%
“…The RARE also lost its regulatory function with the C variant. In our previous study, we found that RXRα can bind directly to the RARE 23 . Our EMSA data show that the C allele can alter the interaction between transcription factors and the sequence element.…”
Section: Discussionmentioning
confidence: 93%
“…observed that rs371954924 in WNT5A reduced gene expression by attenuating the binding affinity of the transcription factor SOX9 43 . In our previous study, we identified a functional RARE in the Cx43 promoter 23 . A genetic variant in the Cx43 promoter was located within the functional RARE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation